PENINGKATAN KEMAMPUAN BERPIKIR KRITIS SISWA MELALUI MODEL PEMBELAJARAN THINK PAIR SHARE (TPS) PADA PENDIDIKAN PANCASILA DI SEKOLAH DASAR - Alfi Syahri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The background of this research is the low critical thinking abilities of students in class V Arafah UPT SDN 002 Kuok student. This research aims to improve students' critical thinking skills through the Think Pair Share (TPS) model in class V Arafah UPT SDN 002 Kuok. This type of research is classroom action research (PTK), which is carried out in two cycles and each cycle consists of two meetings. The subjects of this research were 24 students of class V Arafah. Data collection techniques are carried out using observation and documentation techniques. Data analysis techniques use qualitative data and quantitative data. The results of this research show that the Think Pair Share (TPS) model can improve students' critical thinking skills in Pancasila Education subjects. It can be seen from the achievement of students' critical thinking ability tests in cycle I, meeting I, namely 45.84% and in cycle I, meeting II, it reached 62.5%. The increase in critical thinking skills in cycle II, meeting I reached 70.83% and in cycle II, meeting II reached 83.4%. Thus, it can be concluded that implementing the Think Pair Share (TPS) model can improve the critical thinking skills of class V Arafah UPT SDN 002 Kuok students.